2019
DOI: 10.1534/genetics.119.302665
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila melanogaster PIF1 Helicase Promotes Survival During Replication Stress and Processive DNA Synthesis During Double-Strand Gap Repair

Abstract: PIF1 is a 59 to 39 DNA helicase that can unwind double-stranded DNA and disrupt nucleic acid-protein complexes. In Saccharomyces cerevisiae, Pif1 plays important roles in mitochondrial and nuclear genome maintenance, telomere length regulation, unwinding of G-quadruplex structures, and DNA synthesis during break-induced replication. Some, but not all, of these functions are shared with other eukaryotes. To gain insight into the evolutionarily conserved functions of PIF1, we created pif1 null mutants in Drosoph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 77 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…However, it is also possible that repair proceeds through a break-induced replication (BIR) mechanism. Indeed, we have previously shown that the PIF1 DNA helicase, which is required for BIR in budding yeast [ 46 , 47 ] and promotes BIR in Drosophila [ 48 ], is needed for the efficient repair of a P{w a } -induced gap in the absence of the POL32 protein [ 49 ]. If a BIR-like mechanism is involved in gap repair in this system, then the helicases tested in the current study may also play a role in this type of repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that repair proceeds through a break-induced replication (BIR) mechanism. Indeed, we have previously shown that the PIF1 DNA helicase, which is required for BIR in budding yeast [ 46 , 47 ] and promotes BIR in Drosophila [ 48 ], is needed for the efficient repair of a P{w a } -induced gap in the absence of the POL32 protein [ 49 ]. If a BIR-like mechanism is involved in gap repair in this system, then the helicases tested in the current study may also play a role in this type of repair.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 21 oncogenes were identified, and we selected PIF1 to further confirm its biological function in A549 cells based on the highcontent screening results. PIF1 is a multifunctional helicase and plays important roles in mitochondrial and nuclear genome maintenance, telomere length regulation, unwinding of G-quadruplex structures, and DNA synthesis during break-induced replication [26][27][28]. It is conserved in most eukaryotes and some prokaryotes [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that, like hPIF1, Rrm3 promotes resection across G4 sequences, this seems unlikely because Rrm3 has not been reported to have G4 DNA unfolding activity. Drosophila PIF1 is critical for genome maintenance and the survival of embryos exposed to the replication stalling agent hydroxyurea [ 76 ]. As G4 structures contribute to replication fork stalling, this suggests that Pif1 family helicases may also respond to replication fork stalling at G4 structures in addition to promoting replication through these structures.…”
Section: Pif1 Resolves Replication Barriersmentioning
confidence: 99%
“…Unlike canonical S-phase DNA synthesis, BIR involves conservative DNA synthesis by Polδ in a migrating D-loop [ 164 ]. Yeast, drosophila, and human cells depleted of Pif1 are deficient in BIR, but the depletion of Rrm3 does not affect BIR [ 76 , 142 , 165 ]. It is possible that two Pif1 molecules participate in BIR, with one at the leading edge of the migrating D-loop, which stimulates strand displacement synthesis by Polδ through its interaction with PCNA [ 39 ].…”
Section: Break-induced Replicationmentioning
confidence: 99%